PENGARUH METODE ROLE PLAY TERHADAP PERKEMBANGAN SOSIAL-EMOSIONAL PADA ANAK USIA DINI TK DHARMA WANITA PERSATUAN BLURU KIDUL, KABUPATEN SIDOARJO - Mufarrochah , Hanif; Laili, Nurfi (Journal of Social Science, 2024)
This study aims to determine the influence of role play method on early childhood social emotional development in Dharma Wanita Assosiation Bluru Kidul Kindergarten, Sidoarjo. The method used in this study is a quantitative method with a quasi-experimental approach or pseudo-experiment. This study used a non-randomized pretest-post control group design. With test data collection techniques, observation and documentation. The population in this study amounted to 100 children with a sample of 20 children. The sampling technique uses purposive sampling. The results of the gain score study obtained a sig value (P-velue) of 0.001 < 0.05 which means that the role play method has real effectiveness. Then the results of the hypothesis test obtained a sig (P-velue) value of 0.001 < 0.05, it can be concluded that there is a significant difference before being given treatment and after being given treatment in the form of role-playing methods on the social-emotional development of group A children at Dharma Wanita Assosiation Bluru Kidul Kindergarten, Sidoarjo